Epidemiology of drug-induced liver injury in a University Hospital from Colombia: Updated RUCAM being used for prospective causality assessment (2019)
ABSTRACT: Introduction and aim: Epidemiological information regarding drug-induced liver injury in some Latin American countries remains limited. Therefore, disease prevention and health promotion strategies are imperative to reduce drug-induced liver injuries and its fatal outcomes. This study aimed to collect epidemiological data regarding drug-induced liver injury and identify associated factors in patients admitted to a university hospital in Colombia. Methods and patients: A prospective study was conducted for 1 year to assess the incidence of druginduced liver injury in patients aged >18 years who showed elevated values in liver tests. Data were collected after obtaining informed consentfrom the patients. The updated Roussel Uclaf Causality Assessment Method was applied to assess the causality of drug-induced liver injury. Results: The study included 286 patients with elevated values in liver tests, 18 of whom presented with drug-induced liver injury. The mean age of patients was 54.7 ± 19.1 years. The associated pharmacological groups were anti-infectives and anticonvulsants (isoniazid, rifampicin, nitrofurantoin, phenytoin, and valproic acid), with a total of 15 drugs. The affected patients presented with cytopenia, jaundice, nausea, vomiting, or hepatomegaly. The most common type of liver injury was hepatocellular, and most patients recovered satisfactorily. The number of patients who had highly probable and probable causality grading was 1 and 9, respectively. Conclusion: The incidence of drug-induced liver injury in a university hospital in Colombia was 6%. Comorbidities and concomitant drugs are risk factors for drug-induced liver injury.